Model Strategi Peningkatan Indeks Desa Membangun (IDM) di Kabupaten Ciamis - Ahmad Zaenudin; Ading Rahman Sukmara; Nurdiana Mulyantini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine and describe the strategy model for increasing the Village Development Index (IDM) seen from environmental resilience, economic resilience, and social resilience. This study uses a qualitative descriptive method. The results of the study indicate that the strategy model for increasing the IDM from environmental resilience is still less than optimal in underdeveloped villages and developing villages. Although developing villages are better than underdeveloped villages, there are several problems such as potential disasters that have not been handled properly, especially landslides. In terms of economic resilience, developing village communities have a better diversity of livelihoods than underdeveloped villages. Access to trade facilities and financial institutions is limited in both villages, although developing villages have alternatives through BUMDes. In terms of social resilience, access to education and health in both villages is quite good, although the BPJS membership rate is still low. In terms of housing, developing villages have recorded almost equal access to clean water, sanitation, and electricity, while underdeveloped villages have not reached 100%. Access to information and communication in both villages is available, but not yet optimal.